Screening and characterization of the scFv for chimeric antigen receptor T cells targeting CEA-positive carcinoma - Zhang, Chengcheng; Wang, Linling; Zhang, Qianzhen; Shen, Junjie; Huang, Xia; Wang, Meiling; Huang, Yi; Chen, Jun; Xu, Yanmin; Zhao, Wenxu; Qi, Yanan; Li, Yunyan; et al. (Frontiers in Immunology, 2023)
Carcinoembryonic antigen (CEA) is an attractive target for chimeric antigen receptor T (CAR-T) cell therapy of solid tumors due to its high expression in a variety of tumors, especially gastrointestinal cancers, and strictly restricted expression in a few adult normal tissues. Humanized scFv may reduce humoral and cellular immune responses, and improve the persistence of CAR-T cells. We previously reported a clinical study in which humanized CEA-targeting CAR-T cells achieved a disease control rate of 70% with no off-target or on-target/off-tumor side effects. To improve the therapeutic efficacy of CEA-targeting CAR-T cells, we screened four reported humanized or fully human anti-CEA antibodies (M5A, hMN-14, BW431/26, and C2-45) in terms of affinity, stability, and tonic signal. M5A and hMN-14 CARs displayed higher affinity and more stable CEA binding ability than BW431/26 and C2-45 CARs. In a repeat CEA antigen stimulation assay, M5A showed the best reactivity, including cell proliferation, activation status, and cytokine secretion levels. During in vitro cell culture, M5A CAR-T cells showed a more differentiated phenotype, suggesting greater tonic signal of M5A scFv. MN-14 CAR-T cells had a larger proportion of memory-like T cells. M5A, hMN-14, and BW431/26 CAR-T cells exhibited effective tumor cell lysis and IFN-γ release when cocultured with CEA-positive tumor cells in vitro, correlating with the abundance of CEA expression in target cells. However, C2-45 resulted in almost no tumor lysis or IFN-γ release. In a mouse xenograft model, M5A CAR-T cells displayed better antitumor efficacy without preconditioning. Our study demonstrated that scFvs derived from different antibodies have diverse characteristics. Stable expression and appropriate affinity are likely to result in robust antitumor efficacy. These results highlight the importance of selecting an optimal scFv in CAR-T cell design for effective CEA-targeted therapy.